2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591559
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory rate estimation from multilead directions, based on ECG delineation

Abstract: Estimating the instantaneous respiratory rate (Rr) from the electrocardiogram (ECG) is of interest as respiration direct measurement in clinical situations is often cumbersome. In this study, the Rr was estimated from the same Final Directions of maximum projection (FD) used for multi lead ECG automatic delineation. Power spectral analysis over the directions based on QRS complex main peak and T wave on-set, peak and end spatial loops was used for Rr estimation. On a subset of the Physionet MGH/MF dataset, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…• Extract the main direction of the electric heart vector at a specific phase in the cardiac cycle (e.g., T-wave) [165].…”
Section: Table II Feature-based Techniques For Extraction Of Respiratory Signalsmentioning
confidence: 99%
“…• Extract the main direction of the electric heart vector at a specific phase in the cardiac cycle (e.g., T-wave) [165].…”
Section: Table II Feature-based Techniques For Extraction Of Respiratory Signalsmentioning
confidence: 99%
“…Moreover a strong relation between the respiration and the T wave end based Fit directions of maximum projection (FD) used the by multi lead ECG delineation system (ML) was found in [10]. Taking advantage of this relation, in [11] we have been able to estimate r R with good results from the FD used for T wave end delineation. In this study we aim to combine the information based in FD found for the delineation of QRS peak and T wave peak and end to obtain a single r R estimation.…”
mentioning
confidence: 96%